Analysis of the Salmonella regulatory network suggests involvement of SsrB and H-NS in σE-regulated SPI-2 gene expression - Li, Jie; Overall, Christopher C.; Nakayasu, Ernesto S.; Kidwai, Afshan S.; Jones, Marcus B.; Johnson, Rudd C.; Nguyen, Nhu T.; McDermott, Jason E.; Ansong, Charles; Heffron, Fred; Cambronne, Eric D.; Adkins, Joshua N. (Frontiers in Microbiology, 2015)
The extracytoplasmic functioning sigma factor σE is known to play an essential role for Salmonella enterica serovar Typhimurium to survive and proliferate in macrophages and mice. However, its regulatory network is not well characterized, especially during infection. Here we used microarray to identify genes regulated by σE in Salmonella grown in three conditions: a nutrient-rich condition and two others that mimic early and late intracellular infection. We found that in each condition σE regulated different sets of genes, and notably, several global regulators. When comparing nutrient-rich and infection-like conditions, large changes were observed in the expression of genes involved in Salmonella pathogenesis island (SPI)-1 type-three secretion system (TTSS), SPI-2 TTSS, protein synthesis, and stress responses. In total, the expression of 58% of Salmonella genes was affected by σE in at least one of the three conditions. An important finding is that σE up-regulates SPI-2 genes, which are essential for Salmonella intracellular survival, by up-regulating SPI-2 activator ssrB expression at the early stage of infection and down-regulating SPI-2 repressor hns expression at a later stage. Moreover, σE is capable of countering the silencing of H-NS, releasing the expression of SPI-2 genes. This connection between E and SPI-2 genes, combined with the global regulatory effect of σE, may account for the lethality of rpoE-deficient Salmonella in murine infection.